2018
DOI: 10.1016/j.automatica.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Collective motion under beacon-referenced cyclic pursuit

Abstract: Cyclic pursuit frameworks, which are built upon pursuit interactions between neighboring agents in a cycle graph, provide an efficient way to create useful global behaviors in a collective of autonomous robots. Previous work had considered cyclic pursuit with a constant bearing (CB) pursuit law, and demonstrated the existence of circling equilibria for the corresponding dynamics. In this work, we propose a beacon-referenced version of the CB pursuit law, wherein a stationary beacon provides an additional refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While this line of research has demonstrated the existence of circling equilibria in which agents moved on a common circular trajectory, both the location of the circumcentre of the formation (with respect to some inertial frame) and its size were determined by initial conditions rather than control parameters. To overcome this aspect and to broaden the scope from a design perspective, the work in [13][14][15] introduced a modified version of the CB pursuit law (in the planar setting), wherein the pursuer pays attention to its neighbour as well as to a stationary beacon. The beacon can represent an attractive food source in a biological setting, or some target of interest for an unmanned vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…While this line of research has demonstrated the existence of circling equilibria in which agents moved on a common circular trajectory, both the location of the circumcentre of the formation (with respect to some inertial frame) and its size were determined by initial conditions rather than control parameters. To overcome this aspect and to broaden the scope from a design perspective, the work in [13][14][15] introduced a modified version of the CB pursuit law (in the planar setting), wherein the pursuer pays attention to its neighbour as well as to a stationary beacon. The beacon can represent an attractive food source in a biological setting, or some target of interest for an unmanned vehicle.…”
Section: Introductionmentioning
confidence: 99%